Upaya Meningkatkan Prestasi Belajar PAI Siswa Melalui Pemberian Tugas Berbasis Portofolio : Penelitian Tindakan Kelas pada Siswa Kelas VIII A SMP Negeri 1 Kertasemaya Indramayu) - Muasromatul Azizah (LPPM STAIS Dharma Indramayu, 2019)
This research aims to find out: 1) determine the implementation of portfolio-based assignments to improve PAI learning achievement in class VIII A students of SMP Negeri 1 Kertasemaya Indramayu, 2) improve PAI learning achievement in class VIII A students of SMP Negeri 1 Kertasemaya Indramayu through assignment-based assignments. portfolio. This research is Classroom Action Research (PTK), consisting of three cycles, each cycle consisting of planning, implementation, observation, analysis and reflection. The subjects of this research were students in class VIII A of SMP Negeri 1 Kertasemaya Indramayu who had low learning achievement in PAI subjects due to the lack of variety in learning methods that had been taking place. The researcher then used a learning strategy by giving portfolio-based assignments to improve PAI learning achievement in class VIII A students of SMP Negeri 1 Kertasemaya Indramayu. The data collection technique in this research is to use the test method to determine the level of students' understanding of the concept of Islamic religious education, the observation method to observe the learning process of Islamic religious education through giving portfolio-based assignments (teacher activity, student participation), and the documentation method to find out the names of students. , the number of students and the value of Islamic religious education both before / after being given learning by giving portfolio-based assignments. After taking action through giving portfolio-based assignments, the PAI learning achievement of class VIII A students at SMP Negeri 1 Kertasemaya Indramayu increased. This is shown by the increase in the average student final test assessment in each cycle, namely: cycle I = 6.70, cycle II = 7.10 and cycle III = 7.70. From the results of this research, it is hoped that learning strategies by providing portfolio-based assignments to improve student learning achievement can be applied by teachers of PAI subjects in particular and other subjects in general.